Business trend analysis of RMG industry in context of Bangladesh-A case study - Farhana, Kaniz; Sneha, Zakiya Zohura; Mondol, Subrota; Farin, Faijun; Mahamude, Abu Shadate Faisal (Penerbit Universiti Malaysia Pahang, 2022)
Bangladesh has made a tremendous contribution to RMG (Ready Made Garment) sector since the 1970s. Textiles and apparels consider for about 85% of the total export earnings of Bangladesh. Though it’s quite difficult to mete out the dimension of performance and objection of the RMG sector in Bangladesh but to fulfill the task this study has made a search based on the study of attainable documents. The beauty of this study lies in its way of narration, a sequential way of description. The study discovers that since its inception, the RMG industry contributed significantly to our economy especially during the last three decades. The cross-check analysis has been conducted to compare the last three decades’ export of RMG, specific garments export, GDP, market share, etc to get a lucid idea of the business trend of the RMG industry. These initiatives focus more on the establishment of sound structure, skilled manpower, enhanced market access, access to finance at the competitive interest rate, adaptation with advanced technology as well as institutional development. Therefore, both public and private sectors need to take several preliminaries, independently and collaboratively to overcome these challenges. Moreover, to take control and reserve the golden share of RMG, assured branding needs to be expansive.